2296. Development of a Sequencing-Based Assay for Detection of CMV Antiviral Resistance Mutations to Letermovir in UL56. (26th November 2018) - Grantham, James; Nutt, Jamie; Tyler, Aaron; Bixler, Ellis; Altrich, Michelle; Kleiboeker, Steve
Abstract: Background: Antiviral resistance to human cytomegalovirus (CMV) is a growing concern for immunocompromised patients on prolonged antiviral regimens, and CMV remains the most clinically significant infection following allogeneic hematopoietic-cell transplantation. Letermovir targets subunit 2 of the viral terminase complex (UL56) and is approved for CMV prophylaxis in adult stem cell transplant recipients. Resistance to letermovir is conferred by point mutations in the UL56 gene, and with the potential clinical need for antiviral resistance testing, we have developed a UL56 sequencing assay covering 23 identified resistance mutations. Here we summarize the performance characteristics of the UL56 antiviral resistance assay. Methods: This assay uses automated nucleic acid extraction followed by CMV UL56-specific polymerase chain reaction (PCR). PCR products are subjected to cycle sequencing and capillary electrophoresis, and the resulting sequences are analyzed for the The presence of known resistance mutations between codons 229 and 369 of the UL56 gene. The assay's limit of detection (LOD), precision and accuracy were validated in accordance with accepted regulatory standards using multiple laboratory and clinical CMV strains. Results: The LOD was determined to be 99 IU/mL. Precision was demonstrated with multiple sample replicates over three days of testing, with 100% amino acid concordance within the region of interest (ROI). The assay also accurately identified 100% of amino acids within the ROI of 30 unique CMV-positive de-identified clinical samples. While some polymorphisms were detected, no mutations conferring resistance were identified in the clinical samples tested, which is in agreement with the literature indicating that naturally occurring polymorphisms in the UL56 gene have not been shown to confer resistance to letermovir. Conclusion: The CMV UL56 antiviral resistance assay was shown to be a rapid and sensitive means of detecting mutations conferring letermovir resistance. This expands current CMV antiviral resistance testing, which includes UL54 and UL97 sequencing, and provides physicians with the ability to monitor for the emergence of antiviral resistance mutations to all current FDA-approved anti-CMV drugs. Disclosures: J. Grantham, Viracor Eurofins Clinical Diagnostics: Employee, Salary. J. Nutt, Viracor Eurofins Clinical Diagnostics: Employee, Salary. A. Tyler, Viracor Eurofins Clinical Diagnostics: Employee, Salary. E. Bixler, Viracor Eurofins Clinical Diagnostics: Employee, Salary. M. Altrich, Viracor Eurofins Clinical Diagnostics: Employee, Salary. S. Kleiboeker, Viracor Eurofins Clinical Diagnostics: Employee, Salary.